2009
DOI: 10.1586/erc.09.88
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in ethnic groups: epidemiological and clinical perspectives

Abstract: In the UK and other developed nations, hypertension and its vascular complications are more common in ethnically African and South-Asian communities compared with Europeans. While these conditions are less common in rural India and Africa, they present a rising problem in expanding cities in all developing countries. Hypertension is, therefore, mainly related to environmental and lifestyle factors rather than genetically determined racial differences. Studies in the USA and elsewhere show that the striking dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…Black Africans are known to have elevated BP compared with Caucasians [20], and this was confirmed in the present study. Black participants from the present study also demonstrated a higher prevalence of depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…Black Africans are known to have elevated BP compared with Caucasians [20], and this was confirmed in the present study. Black participants from the present study also demonstrated a higher prevalence of depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…There is limited literature published on ethnic differences in hypertension in this setting but there is substantial literature on the ethnic differences in the prevalence of hypertension elsewhere [47]. The different lifestyles, including occupation, diet, and sedentary behavior may be the most plausible explanation for these significant differences, although genetic factors may have a role to play [48].…”
Section: Prevalencementioning
confidence: 99%
“…First, CCBs are probably more effective in lowering blood pressure in Eastern Asians, because, when compared with the White population, Eastern Asians have high dietary intakes of sodium 5 and are more likely to be salt sensitive. 6 Second, CCBs, compared with other classes of antihypertensive drugs, provide more protection against stroke; 7,8 hence, they are more relevant because the major complication of hypertension in Eastern Asians is stroke rather than myocardial infarction. In the recent Chinese FEVER trial, the incidence of stroke and coronary events was 15.9 and 6.2 per 1000 patientyears, respectively.…”
Section: Introductionmentioning
confidence: 99%